Impact of digital economy on high-quality development: a panel evidence from Chinese provinces - Ma, Hui; Zulkefly Abdul Karim,; Noorasiah Sulaiman,; Abdul Hafizh Mohd Azam, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This paper aims to investigate the impact of the digital economy (DE) on high-quality development (HQD). The two-way fixed effect model is used to examine to what extent the DE affects the HQD using data from 30 provinces in China from 2013 to 2022. The main findings demonstrated that the digital economy significantly affected the high-quality development of China's provinces. In sub-dimension analysis, the digital economy has a significant impact on innovation, coordination, and openness, but does not have a significant incentive effect on greenness and sharing, whereas the four dimensions of the digital economy, namely digital infrastructure, ICT, digital integration, and digital environment, all significantly promote the high-quality development. It is also discovered that the impact of the digital economy on high-quality development is different in three different regions, with the central affected most, followed by the west, and the east being least affected. For the provinces category, the digital economy contributes more to high-quality development in less-developed provinces than in developed ones. The policy implications of this study suggest that the government should prioritize the development of digital infrastructure and digital environments and take into account regional differences in the digital economy to promote coordinated regional development.